STUDENT ENGAGEMENT IN THE LEARNING PROCESS THROUGH ZOOM - Siefanny Puspita Ningrum; Rizqillah Salsabila; Yasyfa Ainan; Wiwik Juwarini Prihastiwi (Proceeding International Symposium on Global Educatiorg Psychology, and Cultural Synergy, 2024)
Online learning through Zoom has become a new reality in education. However, the utilization of technology does not necessarily guarantee effective learning. One crucial factor influencing learning effectiveness is student engagement. Therefore, this study aims to analyze student engagement in the learning process using the Zoom platform based on cognitive, behavioral, and emotional dimensions. This research employed a quantitative descriptive approach with 100 respondents who had participated in online learning via Zoom meetings. Of these respondents, 82% were female, and 18% were male. The research findings revealed that: 1) In terms of cognitive engagement in Zoom meetings, 54% of respondents felt uncomfortable asking questions to the instructor, 83% expressed that a lack of direct interaction with the educator hindered their understanding of the material, and 77% experienced difficulty concentrating during Zoom meetings. 2) Regarding behavioral engagement, 73% of participants took part in quizzes conducted during Zoom classes. In terms of punctuality, 73% arrived on time, and 60% actively asked questions and provided comments during Zoom meetings. 3) Concerning emotional engagement in Zoom learning, 66% of respondents felt a disconnect from the instructor and classmates during Zoom-based learning.